2008
DOI: 10.3354/meps07681
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of dinoflagellate and cyanobacterial harmful algal blooms in southwest Florida coastal waters: dual nutrient (N and P) input controls

Abstract: During July 2006, 2 distinctly different harmful algal blooms (HABs), one dominated by the pelagic red tide dinoflagellates Karenia spp. and the other by the benthic cyanobacterium Lyngbya majuscula, occurred simultaneously in the coastal embayments surrounding Sanibel and Captiva Islands, Florida, USA. The co-occurring HABs were investigated using in situ bioassays with additions of nitrogen (N) and phosphorus (P) alone and in combination to assess nutrient controls of these 'dueling' toxin-producing species.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 48 publications
1
19
0
1
Order By: Relevance
“…The exception to this trend in the St. Lucie Estuary is high rainfall periods associated with high discharges from Lake Okeechobee during intense freshwater HAB events in the lake, leading to freshwater HABs of allochthonous origin in the estuary 18,39 . Similar relationships have been observed in other estuaries 77 , such as the Caloosahatchee estuary in Florida 78 and San Francisco Bay 79 .…”
Section: Resultssupporting
confidence: 82%
“…The exception to this trend in the St. Lucie Estuary is high rainfall periods associated with high discharges from Lake Okeechobee during intense freshwater HAB events in the lake, leading to freshwater HABs of allochthonous origin in the estuary 18,39 . Similar relationships have been observed in other estuaries 77 , such as the Caloosahatchee estuary in Florida 78 and San Francisco Bay 79 .…”
Section: Resultssupporting
confidence: 82%
“…Several studies have reported large blooms of Dapis pleousa (as Lyngbya majuscula ) in coastal locations around Florida, based on secondary metabolites analyses and/or limited molecular data (Capper and Paul , Paerl et al. , Capper et al. , Sneed et al.…”
Section: Discussionmentioning
confidence: 99%
“…The misidentification of these cryptic species is, however, understandable when a polyphasic molecular, chemical, and electron microscopy approach had not been applied until now. Several studies have reported large blooms of Dapis pleousa (as Lyngbya majuscula) in coastal locations around Florida, based on secondary metabolites analyses and/ or limited molecular data (Capper and Paul 2008, Paerl et al 2008, Capper et al 2016, Sneed et al 2017. Likewise, this species has also been reported from other locations in the Caribbean (e.g., Panama, Gutierrez et al 2010), Pacific (e.g., Hawaii, Cardellina et al 1979;Guam, Thacker et al 1997), and Indian Ocean (Madagascar, Singh et al 1999), suggesting that D. pleousa is an abundant, common, and widely distributed cyanobacterium in tropical marine environments as well as subtropical regions during warmer summer periods.…”
mentioning
confidence: 99%
“…Regional and global warming, with an associated increase in temperature and variability in rainfall patterns, causes changes in nutrients, sediment delivery, sediment-water exchange and metabolism, water residence time, and vertical stratification [6,12]. Therefore, ecosystems are subjected to alterations that affect the biotic community, modifying the species composition with the invasion and the establishment of allochthonous populations of Cyanobacteria in freshwater ecosystems [4,15,16]. Lake Iseo should be classified as "warm monomictic", since winter water temperatures never drop below 4 °C.…”
Section: Introductionmentioning
confidence: 99%